Platelet Priming and Activation in Naturally Occurring Thermal Burn Injuries and Wildfire Smoke Exposure Is Associated With Intracardiac Thrombosis and Spontaneous Echocardiographic Contrast in Feline Survivors - Tan, Avalene W. K.; Li, Ronald H. L.; Ueda, Yu; Stern, Joshua A.; Hussain, Mehrab; Haginoya, Satoshi; Sharpe, Ashely N.; Gunther-Harrington, Catherine T.; Epstein, Steven E.; Nguyen, Nghi (Frontiers in Veterinary Science, 2022)
Wildfires pose a major health risk for humans, wildlife, and domestic animals. We previously discovered pathophysiologic parallels between domestic cats with naturally occurring smoke inhalation and thermal burn injuries and human beings with similar injuries; these were characterized by transient myocardial thickening, cardiac troponin I elevation and formation of intracardiac thrombosis. While the underlying mechanisms remain unclear, results from murine models suggest that platelet priming and activation may contribute to a global hypercoagulable state and thrombosis. Herein, we evaluated and compared the degree of platelet activation, platelet response to physiologic agonists and levels of platelet-derived microvesicles (PDMV) in 29 cats with naturally occurring wildfire thermal injuries, 21 clinically healthy cats with subclinical hypertrophic cardiomyopathy (HCM) and 11 healthy cats without HCM (CC). We also quantified and compared circulating PDMVs in WF cats to CC cats. In addition, we examined the association between thrombotic events, severity of burn injuries, myocardial changes, and the degree of platelet activation in cats exposed to wildfires. Flow cytometric detection of platelet surface P-selectin expression showed that cats in the wildfire group (WF) had increased platelet response to adenosine diphosphate (ADP) and thrombin compared to the 2 control groups indicating the presence of primed platelets in circulation. In addition, cats in the WF group had increased circulating levels of PDMV, characterized by increased phosphatidylserine on the external leaflet. Cats in the WF group with documented intracardiac thrombosis had elevated platelet activation and platelet priming in the presence of ADP. While high dose arachidonic acid (AA) mostly resulted in platelet inhibition, persistent response to AA was noted among cats in the WF group with intracardiac thrombosis. Univariate and multiple logistic regression analyses demonstrated that increased platelet response to AA was independently associated with thrombotic events. This is the first study reporting the significant association between platelet priming and intracardiac thrombosis in domestic cats with naturally occurring wildfire-related injuries and smoke inhalation. Further studies are required to delineate additional mechanisms between inflammation and thrombosis, especially regarding platelet primers and the cyclooxygenase pathway.